Development of a non-human primate BCG infection model for the evaluation of candidate tuberculosis vaccines. (January 2018) - Harris, Stephanie A.; White, Andrew; Stockdale, Lisa; Tanner, Rachel; Sibley, Laura; Sarfas, Charlotte; Meyer, Joel; Peter, Jonathan; O'Shea, Matthew K.; Manjaly Thomas, Zita-Rose; Hamidi, Ali; Satti, Iman; et al.
Abstract: The lack of validated immunological correlates of protection makes tuberculosis vaccine development difficult and expensive. Using intradermal bacille Calmette-Guréin (BCG) as a surrogate for aerosol Mycobacterium tuberculosis ( M.tb ) in a controlled human infection model could facilitate vaccine development, but such a model requires preclinical validation. Non-human primates (NHPs) may provide the best model in which to do this. Cynomolgus and rhesus macaques were infected with BCG by intradermal injection. BCG was quantified from a skin biopsy of the infection site and from draining axillary lymph nodes, by culture on solid agar and quantitative polymerase chain reaction. BCG was detected up to 28 days post-infection, with higher amounts of BCG detected in lymph nodes after high dose compared to standard dose infection. Quantifying BCG from lymph nodes of cynomolgus macaques 14 days post-high dose infection showed a significant reduction in the amount of BCG detected in the BCG-vaccinated compared to BCG-naïve animals. Demonstrating a detectable vaccine effect in the lymph nodes of cynomolgus macaques, which is similar in magnitude to that seen in an aerosol M.tb infection model, provides support for proof-of-concept of an intradermal BCG infection model and evidence to support the further evaluation of a human BCG infection model.